2018
DOI: 10.1111/ejn.13817
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing synchrony patterns across cognitive task stages of associative recognition memory

Abstract: Numerous studies seek to understand the role of oscillatory synchronization in cognition. This problem is particularly challenging in the context of complex cognitive behavior, which consists of a sequence of processing steps with uncertain duration. In this study, we analyzed oscillatory connectivity measures in time windows that previous computational models had associated with a specific sequence of processing steps in an associative memory recognition task (visual encoding, familiarity, memory retrieval, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 62 publications
(119 reference statements)
3
42
0
Order By: Relevance
“…() suggests that alpha desynchronization reflects continuous engagement of the visual system during auditory‐visual multisensory integration. However, in the current special issue and elsewhere, multiple empirical studies suggest a more nuanced view on the role of alpha modulation in cognitive processes such as in memory encoding (Portoles et al ., ), memory retention (Portoles et al ., ; Schroeder et al ., ), speech segmentation (Shahin & Pitt, ), task‐set switching (Foxe et al ., ; Portoles et al ., ), and selective auditory attention (Tune et al ., ). Another such example comes from the lesion study reported herein by Piai et al .…”
Section: General Consensus and Controversiesmentioning
confidence: 99%
“…() suggests that alpha desynchronization reflects continuous engagement of the visual system during auditory‐visual multisensory integration. However, in the current special issue and elsewhere, multiple empirical studies suggest a more nuanced view on the role of alpha modulation in cognitive processes such as in memory encoding (Portoles et al ., ), memory retention (Portoles et al ., ; Schroeder et al ., ), speech segmentation (Shahin & Pitt, ), task‐set switching (Foxe et al ., ; Portoles et al ., ), and selective auditory attention (Tune et al ., ). Another such example comes from the lesion study reported herein by Piai et al .…”
Section: General Consensus and Controversiesmentioning
confidence: 99%
“…Various studies have observed that brain rhythms are recruited in a task-specific manner during sensory, motor and higher-cognitive tasks, linking intrinsic brain rhythms to cognitive functions (Engel et al 1992; Singer and Gray 1995; Engel et al 2001; Lakatos et al 2008; Holcombe 2009; Giraud and Poeppel 2012; Lakatos et al 2013; Heusser et al 2016; Portoles et al 2018; Rimmele, Gross, et al 2018; Schroeder et al 2018; VanRullen 2018). For instance, in sighted individuals, the role of the alpha rhythm (~8–12Hz) in cognition is well-established, with posterior alphaand gamma-band oscillations coupling in excitatory-inhibitory cycles (Klimesch et al 2007; Buffalo et al 2011; Jensen et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…One may argue that a limitation or virtue of this LSBM is that it models only one frequency band but not the whole power spectrum of MEG. Yet, MEG is typically analyzed in frequency bands which each seem to play distinct functional roles [3,5,7,25,[62][63][64]. During behavioral tasks as well as resting-state each frequency band tends to produce a different FC pattern [3,7,64].…”
Section: Limitations and Extensionsmentioning
confidence: 99%
“…Yet, MEG is typically analyzed in frequency bands which each seem to play distinct functional roles [3,5,7,25,[62][63][64]. During behavioral tasks as well as resting-state each frequency band tends to produce a different FC pattern [3,7,64]. Moreover, behavioral studies analyze event related synchronization within one frequency band [5,25,65].…”
Section: Limitations and Extensionsmentioning
confidence: 99%
See 1 more Smart Citation